The Fumonisin B1-Fed Rat as a model for liver injury, oval Progenitor') cell proliferation, and carcinogenesis - Lemmer, Eric Richard (Division of Radiology, 2024)
Fumonisin B1 (FB1) is a carcinogenic mycotoxin produced by the fungus Fusarium moniliforme in maize, and is hepatotoxic and hepatocarcinogenic in rats. The goal ofthis dissertation was to characterise the FB1-fed rat as a model for liver injury and carcinogenesis, and to examine the role of oval ('progenitor') cells during these processes. Male Fischer 344 rats were fed FB, 250 mg/kg diet for five weeks, and this basic feeding regimen was modified in individual experiments. Short-term feeding ofFB1 caused a severe 'toxic' hepatitis, apoptosis and regeneration of hepatocytes, fibrosis, proliferation of OV-6 positive oval cells, and formation of GST pi positive hepatic foci and nodules. Oval cells were noted inside some of the hepatic nodules. There were marked increases in the expression of mRNA transcripts for mature TGF-~ 1 and c-myc in livers ofFB1-fed animals. The overexpression of TGF-~ 1 by hepatocytes may be responsible for the prominent apoptosis and fibrosis seen with liver injury due to FB1. Increased expression of c-myc and TGF-~ 1 may cooperate during FB1-induced promotion of liver tumours, possibly by providing an environment that selects for the growth ofTGF-~1-resistant transformed liver cells. In rats given FBI in the presence of dietary iron overload, FBI augmented iron-induced lipid peroxidation in the liver. However, dietary iron loading appeared to protect against the cancerpromoting properties ofFB1, possibly due to a stimulatory effect on hepatocyte regeneration. Long-term feeding ofFB1 caused fibrosis and regenerative nodules, dysplastic hepatic nodules, cholangiofibrotic lesions, intraductal cholangiocarcinomas, and a hepatocellular carcinoma. 2-Acetylaminofluorene enhanced the effects ofFB1 in the liver, presumably by blocking hepatocyte regeneration in response to FB1 toxicity. Proliferating oval cells were found inside/adjacent to GST pi positive lesions, dysplastic nodules, and cholangiofibrotic lesions, suggesting that oval cells may be involved in FB1-induced hepato- and cholangiocarcinogenesis in the liver. Furthermore, the OV-6 antigen was expressed by proliferating oval cells and bile ductules, hepatic nodules, cholangiofibrotic lesions, and cystic lesions, indicating that all of these cells may have a common ('stem') cell of origin. In conclusion, the FB1-fed rat is a promising model for the study of liver injury, oval ('progenitor') cell proliferation, and carcinogenesis.